COMPARATIVE ANTIOXIDANT QUALITY EVALUATION OF UNDERUTILIZED /LESS COMMON SOUTH INDIAN LEGUMES - UMA SUNDARAM; MARIMUTHU M; ANUPAMA V; P. GURUMOORTHI (International Journal of Pharma and Bio Sciences, 2013)
Legumes are the cheapest source of proteins with desirable nutritional qualities like ability to lower serum cholesterol with high fibre content and high concentration of poly-unsaturated fatty acids. In this context, underutilized legumes including tribal pulses viz, Canavalia ensiformis (jack bean), Macrotyloma uniflorum (horse gram) and Phaseolus lunatus (lima bean) were powdered and evaluated for antioxidant property and identification of functional groups of bioactive compounds. Among the legumes studied, jack bean registered higher levels of tannins (0.855 g/100g), flavonoids (0.063 g/100g), alkaloids (0.645 g/100g) and saponins (0.525 g/100g); while horse gram registered higher levels of total free phenolics (1.670g/100g). The antioxidant activity ranged from 0.15µg/mg to 1.02 µg/mg as ascorbic acid equivalents. The free radical scavenging activity of studied legumes with respect to nitric oxide, superoxide, iron (chelating) and reducing power capacity was accounted up to 21.11%, 19.11%, 27.11% & 1.23, respectively. FTIR peaks showed the presence of the compounds like amines, sulfonates, aliphatic organo halogens, and aliphatic and aromatic nitro compounds. Further, mechanistic studies on pharmacological evaluation are needed for commercial exploitation of these legumes as Nutraceuticals.